An Engineering Tool to Screen and Integrate Biomass Valorization Paths in Multiple-Feedstock Biorefineries - Pyrgakis, Konstantinos A.; Kokossis, Antonis C. (Computer Aided Chemical Engineering, 2018)
Biorefineries are the most promising route for the sustainable exploitation of lignocellulosic biomass sources into a wide range of fuels and materials. Value chains include all potential processing routes from raw materials to intermediate and end-chemicals that are possible to enter the biorefinery site. In this scope, process integration techniques are required to evaluate all potential biorefinery structures and reveal promising multiple-product biorefinery solutions with high efficiencies in use of energy and materials. Provided that biorefinery operations subject to seasonal availability of biomass varieties, the design problem additionally requires screening and planning of appropriate biorenewable feedstocks. This work introduces new concepts and representations that incorporate processes and feedstocks as additional degrees of freedom in integration. The proposed methodology investigates synergies among candidate processes, which benefit the biorefinery instead of operating individually, as well as schedules multiple-feedstock operations. A biomass representation maps all process synthesis options along value chains, while a cascade representation is proposed to simultaneously model direct (heat source-to-sink) and indirect (via steam generation-reuse) integration among involved processes of under-construction site. The proposed model (MILP) is explained through real-life biorefinery cases, which involve 15 candidate biorefinery paths and 6 candidate biomass varieties. The model reveals high efficiency biorefining routes and examines preferences on the use of multiple feedstocks minimizing the annual energy cost of under-construction biorefineries.